2011
DOI: 10.1093/jpepsy/jsq126
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: An Ethics Case Study of HIV Prevention Research on Facebook: The Just/Us Study

Abstract: Online social networks are growing in popularity. Conducting research on social media sites requires deliberate attention to consent, confidentiality, and security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 25 publications
1
71
0
2
Order By: Relevance
“…15,16 Previous studies have asked young people about their social media engagements, though often this research has focused on specific "at-risk" groups, such as adolescent parents. 17 Various sexual health interventions have engaged young people via SNS and found some success in doing so, [18][19][20] also noting the difficulties such as the time and resources required to do this well. 18 Research on utilising social media for promoting sexual health typically takes an instrumental approach, asking how public health can reach this population without necessarily consulting young users of SNS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Previous studies have asked young people about their social media engagements, though often this research has focused on specific "at-risk" groups, such as adolescent parents. 17 Various sexual health interventions have engaged young people via SNS and found some success in doing so, [18][19][20] also noting the difficulties such as the time and resources required to do this well. 18 Research on utilising social media for promoting sexual health typically takes an instrumental approach, asking how public health can reach this population without necessarily consulting young users of SNS.…”
mentioning
confidence: 99%
“…2,13,23 Sheana Bull cautions researchers to consider whether health promotion and/or research is welcome in such spaces, and to be mindful of the ethical implications of these interventions. 20 Evers and colleagues further caution that sexual health promotion agencies entering the space of social media and SNS "should not expect to retain control of the meaning and the message" of health promotion content. 24 Social network sites are sites of self-presentation and identity formation.…”
mentioning
confidence: 99%
“…Research in the interactive domain may involve recruiting subjects via SoMe channels such as Facebook (e.g. Balfe et al, 2012;Bull et al, 2011Bull et al, , 2013Child et al, 2014;Kapp et al, 2013;Leonard et al, 2014) or be implemented through SoMe channels to answer specifi c questions (e.g. Quinton, 2013), with subjects being recruited and asked to use SoMe to record refl ections and experiences on blogs or other platforms (e.g.…”
Section: Social Media As Datamentioning
confidence: 99%
“…Initial research has suggested that participants in online studies should be reminded and asked for consent at multiple time points throughout the study, so they do not forget that they are participating in research while using the technology. 2 The decision of how to best inform consumers of the risks associated with using technologies is an important one that still needs to be addressed. …”
mentioning
confidence: 99%
“…Facebook) has created opportunities for researchers to use these technologies in public health research. [1][2][3][4] Scientific, health and engineering standards should inform decision-makers on how and when researchers use mobile technologies for health research and practice, yet few of these guidelines exist. 5 This commentary aims to create initial recommendations to guide researchers' decisions on development and use of mobile technologies for public health research.…”
mentioning
confidence: 99%